Critical power: An important tool for exercise prescription and the assessment of physiological function - Muniz Pumares, D.; Meyler, S. (Experimental Physiology, 2025)
Connections link a sequence of three related research papers. The central article which links the other two papers has been published in Experimental Physiology. In a Connections article, an author (or authors) of the central article outlines its principal novel findings, tracing how they were influenced by the first article and how the central article has contributed to the developments made in the third article. The author(s) may also speculate on the direction of future research in the field. Connections articles aim to set the research in a wide context.